Tinea capitis caused by Trichophyton tonsurans among adults: Clinical characteristics and treatment response. Issue 2 (27th October 2022) - Galili, Eran; Goldsmith, Tomer; Khanimov, Israel; Arbel, Chen; Sharvit, Sharon; Lyakhovitsky, Anna; Shemer, Avner; Barzilai, Aviv; Astman, Nadav
Abstract: Background: Trichophyton tonsurans tinea capitis has become a growing epidemiological concern. Yet, its clinical manifestations and treatment response, specifically among adults, have only been described among small sample size studies. Objective: To assess clinical manifestations and treatment outcome of T. tonsurans tinea capitis among adults. Patients and Methods: A retrospective cohort study was carried out among 111 adults with T. tonsurans tinea capitis. Diagnosis was confirmed by fungal culture or polymerase chain reaction. Examinees' demographics, disease characteristics and treatment response were measured. The risk factors for the treatment failure were evaluated. Results: The mean age was 20.1 years (±3.1), with men (98.2%) outnumbering women. The follow‐up lasted 12.2 months (±5.6). The majority of T. tonsurans tinea capitis was seen in the occipital area (87.6%). In 78.9% of the cases, the scalp manifestation was non‐inflammatory (scaly plaques and papules:76.1% and seborrhoea‐like: 2.8%). 21.1% of cases presented with inflammatory tinea capitis (21.1%; Kerion: 10.1% and pustular: 11%). Concomitant involvement of other than scalp areas was common: tinea corporis was seen in 38.7% of the cases; tinea faciei and barbae in 24.3%; nape and anterior neck in 76.6% and 2.7% of the cases, respectively. An adequate treatment course with oral terbinafine resulted in 83.2% clinical cure rate. Treatment failure was significantly associated with concomitant tinea corporis (odds ratio 3.9; 95% confidence interval 1.3–12.1, p ‐Value< .02). Conclusion: The most common clinical presentation of T. tonsurans tinea capitis included occipital scaly plaques and papules with concomitant non‐scalp lesions. Oral terbinafine was found to be highly effective. Concomitant tinea corporis increased the risk for treatment failure.